(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India’s economic policy reforms, taken in the sense of historic economic failures in 1990-1991 and some remarkable shifts in the global economic system, have changed the overall structure of the Indian economy since 1991. The reforms developed to free up the market, make it more efficient, bring the government out of its vast mode of control, encourage the Member States to take greater responsibility for the management of economic relations and to establish a kind of rivalry between countries for external investors. Liberalization, Privatization and Globalization (LPG) policies were designed to transform the Indian economy into a quickly expanding and internationally competitive economy. The series of reforms in the industrial, trade and financial sectors also rendered the economy more productive.In July 1991, the Government has continuously followed the strategy of attracting more international investment to increase the availability of capital in infrastructure and other vital fields of the economy. The idea of globalization implies the integrating of the world economies through uninhibited trade and financial flows and through reciprocal transfers of technology and information. Several policy initiatives are being introduced to lure international funds, company names, and FIIs to direct and portfolio investment. In later years, the liberalization initiatives found in the new economic strategy were accompanied by a set of measures to further liberalize the domestic political structure against FDI. A new foreign investment policy was developed that stipulated the acceptance of FDI proposals by three thirds (a). Automatic approval framework of RBI (b). Industrial Approval Secretariat (SIAs) for projects outside the jurisdiction assigned to RBI, and (c). Board for Foreign Investment Promotion (FIPB), an organization formed to invite, negotiate and promote FDI.